Konsep Kota 15 Menit : Peluang dan Tantangan Penerapannya pada Kota Pulau - Risal Rasyid; Pieter Thomas Berhitu; Elvira Florensia Metekohy (Syntax Corporation Indonesia, 2024)
The Banda Neira Islands possess significant cultural potential, yet many historical buildings are neglected, and accessibility is limited. With an area of just 3 km², planning that prioritizes pedestrians and cyclists is necessary. This study aims to explore the opportunities and challenges of implementing the 15-Minute City concept in Banda Neira. A qualitative research method is employed, beginning with an assessment of the physical and non-physical conditions in the urban area, particularly aspects related to the 15-Minute City components. The study finds that adjusting facilities based on population density is crucial for supporting the 15-Minute City principle, with high-density areas requiring more facilities, while low-density areas need better accessibility. The current layout allows access within 15 minutes on foot or by bicycle. The diversity of facilities supports social integration, but further digital technology implementation is needed to enhance service access and overall quality of life.